Karyological Analysis of the Subfamily Chrysomelinae (Coleoptera: Chrysomelidae) - Eduard Petitpierre (Cutting Edge Research in Biology Vol. 5, 2023)
This chapter wants to update the karyotypic data in the Chrysomelinae subfamily to improve our cytogenetic and evolutionary knowledge on the chromosome numbers, sex-chromosome systems and chromosomal architecture of 259 species and chromosomal races in the seven present subtribes. The subfamily has shown a wide range of diploid numbers from 2n = 12 to 2n = 50, and four types of male sex-chromosome systems, with the “parachute-like” ones, Xyp and XYp, clearly prevailing (81.1%), but with the X0 well-represented too (17.4%). The modal haploid number is n = 12, though it is not the presumptive most plesiomorph for the whole subfamily because in the subtribe Timarchina of Timarchini tribe, the modal number is n = 10 (51.2%), in agreement with the ancestral number for the Polyphaga suborder of Coleoptera, and in the subtribe Chrysomelina of the tribe Chrysomelini, is n = 17 in all the so far studied 35 species of this taxon. The karyotypes of 66 species of ten genera are analyzed by measuring the relative length of size for each chromosome of them. The degree of asymmetry in size of their chromosomes was reported from the standard deviations (SD) of relative sizes which showed a negative correlation with the haploid chromosome numbers (r = - 0.29), thereby the karyotypes of high chromosome numbers are in general more symmetrical than those of low numbers. Most species of Chrysolina of the same subgenus share the same chromosome number and sex-chromosome system, but differ in the amount of major chromosome arms (FN = fundamental number). A striking exception to this agreement between karyology and taxonomy are the species of subgenus Stichoptera of Chrysolina, which have a wide variation in their diploid numbers from 2n = 22 to 2n = 34 chromosomes but sharing asymmetric karyotypes. All these close karyotypic similarities shown among species of Chrysolina belonging to the same subgenus are supported by the molecular phylogenetic trees based on DNA sequences of combined nuclear and mitochondrial genes. Some genera of Chrysomelinae are highly variable in the chromosome numbers of their species, namely Chrysolina, Cyrtonus and Timarcha, while others are remarkably conservative, such as Calligrapha (except a few polyploid parthenotes), Leptinotarsa and Oreina, and these differences are discussed. The scarce results obtained on C-banding of heterochromatin, satellite DNA and nucleolar organizing regions (NORs) support a pericentromeric, and less often also, distal location of small amounts of heterochromatin, common widespread species-specific satellite DNAs, and only a single NOR, mostly in an autosomic pair. The genome sizes in 20 species of this subfamily range from 1C = 0.20 pg to 1C = 3.69 pg and they are not related with chromosome numbers, though the species of subtribes Timarchina and Chrysolinina plus Leptinotarsa decemlineata (Colorado potato beetle) seem to have higher genome sizes than the few checked of Chrysomelina subtribe.